Diagnosis about inferential reasoning in undergraduate students of the economic management area - Sandoval Bravo, Salvador; Celso Arellano, Pedro Luis; Gualajara Estrada, Víctor Hugo (IE Revista de Investigación Educativa de la REDIECH, 2021)
Within the forefront research areas in the field of statistical education is located the inferential reasoning, as a fundamental tool for decision-making; factor that accentuates its importance in the case of economics and management careers where future professionals must test hypotheses, build confidence intervals and make estimates on populations based on data referring to representative samples. In this sense, the aim of this work is to measure the inferential reasoning of undergraduate students of the Economics-Management area of the University of Guadalajara to diagnose and identify strengths and opportunity areas, which can be used in the implementation of pertinent solutions both in the pedagogical and disciplinary aspects, and thus increase the future performance of students. For this, the CAOS-4 exam was applied to a sample of 326 students; such instrument has been statistically validated for university students and allows determining the level of inferential reasoning. The results found show that students have problems in identifying and formulating hypotheses, they do not understand the probabilistic nature of the conclusions of statistical inference, they misinterpret the confidence intervals and the margin of error.